Bundling Parametric Insurance to Build Climate Risk Resilient Community: Experience from IBFI Application in Zambia - Umer, Yakob; Amarnath, Giriraj; Padhee, Suman Kumar; Makungwe, Mirriam (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This presentation provides an overview of parametric insurance, explaining what it is, how it works, and its potential benefits for managing risk in sectors vulnerable to climate-related and other catastrophic events.